TESTING HALAL LABELS, PRODUCT QUALITY, CELEBRITY ENDORSER AND REFERENCE GROUP OF WARDAH PURCHASE DECISIONS - Ginanjar Rahmawan; Vita Putri Banwuati (Fakultas Bisnis, 2020)
The increasingly fierce competition in the cosmetics industry requires companies to increase product excellence in order to compete. Wardah is a cosmetics that has the highest growth reaching 25%. This research uses quantitative research methods using a questionnaire. The population in this study is Wardah Lipstick consumers in Solo. Samples taken in this study were 96 respondents with non probability sampling techniques, namely accidental sampling. This study aims to determine the effect of halal labels, product quality, celebrity endorsers and reference groups on purchasing decisions Wardah Lipstick. The data analysis technique used in this study is multiple linear regression analysis techniques processed with SPSS 16 applications. The results of this study are halal labels, product quality, celebrity endorsers and reference groups have a positive and significant effect on purchasing decisions Wardah Lipstick.